TOKOH ORANG TUA DAN REFLEKSI POLITIK ORDE BARU DALAM NOVEL-NOVEL KARYA KUNTOWIJOYO - Kusmarwanti Kusmarwanti (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis study aims to describe the characterization of the elderly, intertextual relationsof the characters of the elderly with Ronggowarsito and Nabi Hizdir, and reflection onissues of the New Order politics in Kuntowijoyo’s novels. The data sources were twonovels by Kuntowijoyo, namely (a) Mantra Pejinak Ular and (b) Wasripin dan Satinah.The results of the study are as follows. First, the characterization of the elderly is madethrough two ways, namely the physical and spiritual modes. Second, the character of theelderly in Mantra Pejinak Ular has an intertextual relation with Ronggowarsito and that inWasripin dan Satinah has an intertextual relation with Nabi Hidzir. Third, the characters ofthe elderly reflect issues of the New Order politics, including: (a) the image of the rulingparty to win in the general election, (b) the loyalty to the ruling party, (c) the arrest andassassination of political opponents, and (d) the economic monopoly and signs of thedownfall of the ruler.